Menggali Potensi Model Inkuiri Terbimbing dalam Membentuk Kemampuan Berpikir Kritis Peserta Didik pada Pembelajaran Biologi - Nasywa Azzahra, Nasywa (Papanda Publisher, 2024)
The challenges faced in learning biology today are the low critical thinking skills of students and the lack of application of student-centered learning models. Through guided inquiry, students are given the opportunity to be actively involved in learning by asking questions, designing experiments, collecting and analyzing data, and drawing conclusions. This study aims to explore the potential of the guided inquiry model in shaping students' critical thinking skills in learning biology. This research was conducted with a literature review of articles in international journals, international seminar proceedings, and SINTA accredited journals. The results of the analysis showed that the guided inquiry model has significant potential in developing students' critical thinking skills. Guided inquiry can facilitate students in building concepts through an active inquiry process. Thus, the application of this model has the potential to broaden learners' horizons while developing higher-order thinking skills that are indispensable in the 21st century.